Predictors and processes of satisfaction with work–family balance: Examining the role of personal, work, and family resources and conflict and enrichment. Issue 1 (29th April 2019) - Wayne, Julie H.; Matthews, Russell; Crawford, Wayne; Casper, Wendy J.
Abstract: Drawing from resource‐based theories, we conduct two studies to investigate the unique and relative importance of personal (e.g., resilience, proactive health behaviors), work, and family resources (i.e., enriched job and family roles, work and family support) to balance satisfaction, and the mediating roles of conflict and enrichment. We test our hypotheses in Study 1 using a cross‐sectional survey of 216 employees and in Study 2 using a time‐lagged survey over 3 months with 220 employees. Across both studies, work and family resources (e.g., enriched job and family characteristics, work and family support) were positively related to balance satisfaction. In general, work resources were more relevant to balance satisfaction than were personal or family resources. In terms of processes, work resources relate to less work‐to‐family conflict and greater work‐to‐family enrichment which in turn, relate to greater balance. In contrast, the family‐to‐work directions of conflict and enrichment were just weakly related to balance. Across the two studies, findings regarding the role of personal resources were mixed. We discuss how these findings expand our understanding of work–family balance and the practical implications for human resource practitioners.